Fast return to sports and high level of activity after cementless Oxford unicompartmental knee arthroplasty - Panzram, Benjamin; Mandery, Mira; Reiner, Tobias; Walker, Tilman; Merle, Christian; Gotterbarm, Tobias (The journal of knee surgery, 2021)
Physical activity is essential for overall health. For patients undergoing knee arthroplasty, questions about the implant's suitability for sports arise. The general recommendations for physical activity with knee replacements are often based upon experts' opinions, with a lack of scientific data. This study was performed at an independent high-volume center and aimed to investigate what level of activity patients can achieve and how they perform with a well-functioning cementless unicompartmental knee replacement (UKR). Possible differences in outcome in regards to patients' body mass index (BMI) were also examined. A total of 228 knees treated with cementless Oxford UKR (OUKR) were followed up after a mean of 37.1 months. Tegner's and UCLA (University of California, Los Angeles) scores were obtained to assess the level of physical activity. The Schulthess Clinical Activity Questionnaire was assessed for detailed information on practiced sports, and the SF-36 questionnaire was evaluated to analyze patients' quality of life. The return to activity rate was 92.9%. In total, 64% of the physically active patients had already taken up sports within 3 months after surgery. Mean Tegner's score was at 3.5, and mean UCLA score was at 6.3. High impact sports were not performed very often after surgery. Higher BMI showed a negative correlation with the numbers of sports (rsp = −0.289) as well as Tegner's (rsp = −0.222) and UCLA (rsp = −0.383) scores. The SF-36 scores were comparably good to those in an age-equivalent standard reference group. In conclusion, cementless OUKR allows a fast return to activity with a high level of physical exercise. Patients with increased BMI tend to practice less types of sports with decreased activity scores.